Sugarcane bagasse cellulose/HDPE composites obtained by extrusion - Mulinari, Daniella Regina [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila H. [UNESP]; da Silva, Maria Lucia C. P.; da Cruz, Tessie Gouvea [UNESP]; Saron, Clodoaldo (Elsevier B.V., 2009)
Natural fibers used in this study were both pre-treated and modified residues from sugarcane bagasse. Polymer of high density polyethylene (HDPE) was employed as matrix in to composites, which were prodUced by mixing high density polyethylene with cellulose (10%) and Cell/ZrO(2)center dot nH(2)O (10%), using an extruder and hydraulic press. Tensile tests showed that the Cell/ZrO(2)center dot nH(2)O (10%)/HDPE composites present better tensile strength than cellulose (10%)/HDPE composites. Cellulose agglomerations were responsible for poor adhesion between fiber and matrix in cellulose (10%)/HDPE composites. HDPF/natural fibers composites showed also lower tensile strength in comparison to the polymer. The increase in Young's modulus is associated to fibers reinforcement. SEM analysis showed that the cellulose fibers insertion in the matrix Caused all increase of defects, which were reduced When modified cellulose fibers were Used. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Fibers; Polymer-matrix composites; Mechanical properties; scanning electron microscopy (SEM); Extrusion